Cardiomyocyte Protection by Hibernating Brown Bear Serum: Toward the Identification of New Protective Molecules Against Myocardial Infarction - Givre, Lucas; Crola Da Silva, Claire; Swenson, Jon E.; Arnemo, Jon M.; Gauquelin-Koch, Guillemette; Bertile, Fabrice; Lefai, Etienne; Gomez, Ludovic (Frontiers in Cardiovascular Medicine, 2021)
Ischemic heart disease remains one of the leading causes of death worldwide. Despite intensive research on the treatment of acute myocardial infarction, no effective therapy has shown clinical success. Therefore, novel therapeutic strategies are required to protect the heart from reperfusion injury. Interestingly, despite physical inactivity during hibernation, brown bears (Ursus arctos) cope with cardiovascular physiological conditions that would be detrimental to humans. We hypothesized that bear serum might contain circulating factors that could provide protection against cell injury. In this study, we sought to determine whether addition of bear serum might improve cardiomyocyte survival following hypoxia-reoxygenation. Isolated mouse cardiomyocytes underwent 45 minutes of hypoxia followed by reoxygenation. At the onset of reoxygenation, cells received fetal bovine serum (FBS, positive control), summer (SBS) or winter (WBS) bear serum, or adult serums of other species as indicated. After 2 hours of reoxygenation, propidium iodide staining was used to evaluate cell viability by flow cytometry. Whereas 0.5% SBS tended to decrease reperfusion injury, 0.5% WBS significantly reduced cell death, averaging 74.04±7.06% versus 79.20±6.53% in the FBS group. This cardioprotective effect was lost at 0.1%, became toxic above 5%, and was specific to the bear. Our results showed that bear serum exerts a therapeutic effect with an efficacy threshold, an optimal dose, and a toxic effect on cardiomyocyte viability after hypoxia-reoxygenation. Therefore, the bear serum may be a potential source for identifying new therapeutic molecules to fight against myocardial reperfusion injury and cell death in general.